THE INFLUENCE OF LABOR ABSORPTION PROBLEMS ON THE UNEMPLOYMENT RATE IN NORTH SUMATRA PROVINCE IN AN ISLAMIC PERSPECTIVE - Suaidah Suaidah; M. Ridwan; Nur Ahmadi Bi Rahmani (Jurnal As-Salam, 2023)
This study aims to analyze the influence of labor absorption issues on the unemployment rate in North Sumatra Province from an Islamic perspective. The research method used is quantitative, utilizing secondary data from the Central Statistics Agency of North Sumatra Province and relevant literature. The variables analyzed include Gross Regional Domestic Product (GRDP), population size, provincial minimum wage, education level, and labor absorption. The research findings indicate that GRDP is not intervened by labor absorption concerning unemployment. The population size indirectly influences unemployment, with labor absorption as an intervening variable. Provincial minimum wage and education level directly affect unemployment without being intervened by labor absorption. From an Islamic perspective, balancing these labor factors to reduce unemployment and achieve socio-economic justice in North Sumatra Province is important. These conclusions have several important implications. First, there needs to be attention given to regional economic growth to impact labor absorption positively. Second, wise population management is crucial to optimize job availability. Third, provincial minimum wage and education level play a significant role in reducing unemployment. Fourth, applying Islamic values in managing labor, including ethical and just aspects, is important. These implications are expected to provide guidance and recommendations for the government and stakeholders in addressing unemployment issues in North Sumatra Province.